(untitled) (Lundiana: International Journal of Biodiversity, 2002)
Coarazuphium pains sp. n., a troglobitic Carabidae, is described and illustrated from a male specimen collected in the Tabocas III cave, at Pains, Minas Gerais, Brazil. This species, like C. bezerra, differs from the remaining species of the genus Coarazuphium by having two pairs of setae close to the posterior margin of the head, and differs from all others by having two pairs of setae at the ventral surface of the protorax and by having the apex of the elytra not sinuous.